2014
DOI: 10.1111/cei.12194
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, pathogenesis and treatment of myositis: recent advances

Abstract: Diagnosis, pathogenesis and treatment of myositis: recent advances OTHER ARTICLES PUBLISHED IN THIS SERIESParaneoplastic neurological syndromes. Clinical and Experimental Immunology 2014, 175: 336-48. Disease-modifying therapy in multiple sclerosis and chronic inflammatory demyelinating polyradiculoneuropathy: common and divergent current and future strategies. Clinical and Experimental Immunology 2014, 175: 359-72

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 107 publications
(131 reference statements)
1
99
0
10
Order By: Relevance
“…It has been reported that the average age of onset in SRP-correlated autoimmune necrotizing myopathy is approximately 50 years old (Carstens and Schmidt, 2014), which is in agreement with results from our present study, where peak onset age was found to be between 51-60 years of age.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that the average age of onset in SRP-correlated autoimmune necrotizing myopathy is approximately 50 years old (Carstens and Schmidt, 2014), which is in agreement with results from our present study, where peak onset age was found to be between 51-60 years of age.…”
Section: Discussionsupporting
confidence: 94%
“…Although their efficacy has never been confirmed in a randomized controlled trial (RCT), corticosteroids are the traditional first-line treatment for DM, PM, and OS once the diagnosis has been established and other disorders that can mimic an IMIM have been excluded [6,37,38]. It is usual to start treatment with oral prednisolone at a dose of~1 mg/kg/day and it is preferable to avoid using higher doses because of the greater risk of steroid side effects.…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…Previous reviews have discussed the practical aspects of managing ongoing therapy and have emphasized the importance of not continuing high doses of steroids for too long and balancing this against not tapering the dose too quickly. They advocate the introduction of an immunosuppressive agent such as methotrexate, azathioprine, or mycophenolate earlier rather than later as a steroid-sparing strategy [34,[38][39][40][41]. Oral pulse therapy with dexamethasone (monthly cycles of 40 mg/ day for 4 consecutive days) has been suggested as an alternative to prednisolone and has been shown to be as effective in a RCT and to have a more favorable side effect profile, but the time to relapse was shorter with dexamethasone [42].…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…Inclusion body myositis (IBM) is a progressive slow‐onset inflammatory myopathy that is characterized by the concomitant presence of multi‐focal myofiber‐surrounding lymphocytic infiltrates as well as vacuolar myodegeneration 1, 2, 3, 4. Together with dermatomyositis (DM), polymyositis (PM), necrotizing autoimmune myositis (NAM) and overlap myositis (OM), IBM belongs to the heterogenous group of inflammatory myopathies and, amongst individuals 50 years of age and older, it is considered as a relatively frequent disorder 3, 5.…”
Section: Introductionmentioning
confidence: 99%